Reguliertes Abenteuer Missionarinnen in Südafrika nach 1945 - Gugglberger, Martina (2014)
The book focuses on german speaking catholic missionary sisters who came to South Africa after 1945. In three chapters (space of origin, convent space, missionary space) the life stories are interpreted as an "adventure with a rule". The group portrait shows motivations, daily life and experiences of one of the last generations of missionary women.